Monitoring the dual time and temperature of meals transported to dinner in deprivation of liberty institutions (Research, Society and Development, 2021)
Food and Nutrition Units (UAN) are places dedicated to the preparation and supply of meals balanced in nutrients, following the profile of the clientele. International human rights treaties include two dimensions that are indivisible from the Human Right to Adequate Food (DHAD), being the rights not to be hungry and to consume adequate food. is well accepted. As foods are considered vehicles of toxic agents, they must be subjected to practices that prevent the spread of diseases. For this, there are measures such as checking the binomial time x temperature that help to prevent microbiological proliferation. This study aimed to analyze the time x temperature binomial of meals transported to dinner at institutions of deprivation of liberty in the Metropolitan Region of Fortaleza in the state of Ceará. The sample consisted of 50 temperature collections per day, for 8 days, non-sequentially, totaling 400 samples. The meals consisted of a protein option, a side and a garnish, and in 4 of the 8 days, a cooked salad option produced for dinner was served. The results obtained indicated that only 7.3% of the 400 samples were found to be below 60°C at the time of receipt, however, during the filling of the hot dishes, 100% had temperatures above those recommended by law.